Relations between the levels of moderate to vigorous physical activity, BMI, dietary habits, cognitive functions and attention problems in 8 to 9 years old pupils: network analysis (PACH Study) - Jelena Raudeniece; Edmunds Vanags; Ilze Justamente; Dana Skara; Per Morten Fredriksen; Iain Brownlee; Dace Reihmane (BMC, 2024)
Abstract Background Physical activity (PA) and dietary habits (DH) play a crucial role on quality of life and health outcomes from various aspects. Methods This study aims to investigate the relations between recommended daily levels of moderate to vigorous physical activity (MVPA) in 8 to 9 year old pupils, and their body mass index (BMI), DH, cognitive functions and attention problem scores by network analysis. Study participants were split into two groups based on their MVPA levels on weekdays. Results Our findings suggest that children who reach recommended MVPA levels consume more vegetables and fruits, eat breakfast more frequently, have better motor speed and lower impulsivity score. Conclusions The number of interlinkages between various parameters in network structure for children who do not reach recommended MVPA levels is greater and more intense, highlighting the differences between the groups and suggesting that different interventions and approaches to improve/change lifestyle habits might be used.